Prevalence and Trends of Oral Diseases in Elderly Patients at Tripoli University Hospital: A 20-Year Retrospective Analysis - Eman Aga; Ebtesam Aldieb (AlQalam Journal of Medical and Applied Sciences, 2025)
It is now well recognized that there has been a revolution in the age pyramid of many societies, and within a very short time, there will be more people over 60. This is because of a considerable increase in the expectation of life. The current study evaluated retrospectively the frequency and prevalence of elderly patients’ lesions recorded from the Pathology Department and Oral Maxillofacial Department database of Tripoli University Hospital, Tripoli, Libya from 2002 to 2022 year. The total number of reports was 2366 biopsies. The cross-sectional study included patients aged 60 and over. An oral and maxillofacial pathologist revised all histopathologic diagnoses. The study used SPSS version 25 software for data management, and analysis, employed basic descriptive statistics and bivariate analysis to examine the relationship between oral lesions prevalence and demographic factors like age and gender, with a p-value of <0.05. The percentage of oral and maxillofacial lesions in older patients during the period 2002 to 2022 was approximately 7.4%. Regarding gender distribution, 50.9% of the patients were male and 49.1% were female. The average age for females was 68.33 ± 6.449 years, and for males, it was 68.28 ± 7.399 years. Inflammatory lesions were the most common (40.7%) of the cases. Followed by autoimmune diseases (13.9%) while odontogenic cysts, salivary gland disease, and malignant tumors showed the same percentage (9.3%). According to the study’s findings on the frequency of oral lesions in geriatrics. Knowledge of clinical signs and histopathology of oral cavity disease is necessary for prevention, early diagnosis, and correct treatment plan. لقد أصبح من المعترف به الآن أن هناك ثورة في الهرم العمري للعديد من المجتمعات، وخلال فترة قصيرة جدًا، سيكون هناك المزيد من الأشخاص الذين تزيد أعمارهم عن 60 عامًا. ويرجع ذلك إلى الزيادة الكبيرة في توقعات الحياة. قامت الدراسة الحالية بتقييم بأثر رجعي تواتر وانتشار آفات المرضى المسنين المسجلة من قسم علم الأمراض وقاعدة بيانات قسم الوجه والفكين في مستشفى جامعة طرابلس، طرابلس، ليبيا من عام 2002 إلى عام 2022. وبلغ العدد الإجمالي للتقارير 2366 خزعة. وشملت الدراسة المقطعية المرضى الذين تتراوح أعمارهم بين 60 وما فوق. قام أخصائي أمراض الفم والوجه والفكين بمراجعة جميع التشخيصات التشريحية المرضية. استخدمت الدراسة الإصدار 25 من برنامج SPSS لإدارة البيانات وتحليلها، واستخدمت الإحصائيات الوصفية الأساسية والتحليل ثنائي المتغير لفحص العلاقة بين انتشار الآفات الفموية والعوامل الديموغرافية مثل العمر والجنس، بقيمة p <0.05. بلغت نسبة آفات الفم والوجه والفكين لدى المرضى الأكبر سناً خلال الفترة من 2002 إلى 2022 حوالي 7.4%. وفيما يتعلق بالتوزيع حسب الجنس، فإن 50.9% من المرضى ذكور و49.1% إناث. وكان متوسط العمر للإناث 68.33 ± 6.449 سنة، وللذكور 68.28 ± 7.399 سنة. وكانت الآفات الالتهابية الأكثر شيوعا (40.7٪) من الحالات. تليها أمراض المناعة الذاتية (13.9%)، في حين أظهرت الأكياس السنية، وأمراض الغدد اللعابية، والأورام الخبيثة نفس النسبة (9.3%). ووفقا لنتائج الدراسة حول تواتر الآفات الفموية لدى كبار السن. إن معرفة العلامات السريرية والتشريح المرضي لمرض تجويف الفم أمر ضروري للوقاية والتشخيص المبكر وخطة العلاج الصحيحة